(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article reflects on the expressive function of language as well as its importance in artistic speech. Also, the concepts of emotionality and expressiveness in speech are compared, these terms are explained, information is given about linguistic means that ensure the effectiveness of speech.